Creating Web Sites Bible - Crowder Philip (Wiley, 2008)
If you want to build your own Web site in a 2.0 world, you've come to right place. From facing HTML without fear to adding new ?air with multimedia, interactivity, and blogging, this comprehensive guide provides you with everything you need. Loaded with nearly a thousand pages of invaluable techniques and step-by-step instructions, this is your one-stop resource for designing a site, taking it live, keeping it fresh, and moving into the world of e-commerce.